Strengths-Based Approach dan Penguatan Perempuan Melalui Kemandirian Sosial-Ekonomi dalam Wewujudkan Resiliensi Masyarakat di Daerah Tpst (Tempat Pembuangan Sampah Terakhir) Ngablak-Piyungan, Bantul - Rodiah, Ita; Zuhriana, Desi (Proceedings of Annual Conference on Community Engagement, 2022)
The COVID pandemic has had a significant impact in many areas, including social and economic areas. Women have a double burden, in the social role and economic structure, namely domestic and public roles that help the family economy, sometimes even as the head of the household. To increase women’s socio-economic independence, they must be equipped with the knowledge and skill to maximize their role and become more prosperous. This community service is based on the practical implementation of University Community Engagement (UCE) in the society, particularly among women in the Ngablak-Piyungan TPST area of Bantul. This community service aims to strengthen socio-economic independence by fostering community resilience, particularly among women, in the Ngablak-Piyungan TPST area, Bantul. Due to a lack of access to market information and technology, capital, human resource, network, and gender-based awareness among the TPST society. This strengthening in the context of community service is designed using strengths-based approach, an education and training approach, in the Ngablak-Piyungan TPST area of Bantul. These are needed the most because education and training play a strategic role in improving the quality of resources. Strengthening in the context of community service for women in the Ngablak-Piyungan TPST area of Bantul was declared successful, both practically and empirically. This is demonstrated by the growing positive response and the occurrence of economic and social improvements that benefit women in the Ngablak-Piyungan TPST area of Bantul. It is possible to conclude that community service activities provided by women’s strengthening programs have a significant impact on social resilience.